A complex case of low-phospholipid-associated cholelithiasis syndrome. - Figueiredo, LM (2020)
The low-phospholipid-associated cholelithiasis (LPAC) syndrome is a form of symptomatic and recurring cholelithiasis occurring in young adults, associated with mutations in the ABCB4 gene. It is a clinical syndrome characterized by at least two of the following criteria: age at onset of biliary symptoms below 40 years, intrahepatic echogenic foci or microlithiasis and recurrence of biliary symptoms after cholecystectomy. In the rare cases progressing to end-stage liver disease, a liver transplant may be indicated. We report a case of a 40-year-old female patient with clinical criteria for LPAC syndrome and with ABCB4 gene mutation. She had a complex history of choledocholithiasis recurrence despite treatment with ursodeoxycholic acid and multiple therapeutic endoscopic retrograde cholangiopancreatography, and she developed portal vein thrombosis.